PENGARUH PERBANDINGAN MOLAR DAN DURASI REAKSI TERHADAP RENDEMEN BIODIESEL DARI MINYAK KELAPA (Coconut Oil) - Pramitha, Risa Inggit; Haryanto, Agus; Triyono, Sugeng (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2017)
This study aims to determine the effect of the molar ratio of oil : methanol and duration of the reaction on the yield of biodiesel produced from palm oil transesterification. The transesterification reaction is carried out using coconut oil at 60 Â°C and 0.5 grams of NaOH catalyst. The method is a completely randomized design with a combination of two factors, namely the molar ratio and the duration of the reaction. The molar ratio consists of four levels (1: 3, 1: 4, 1: 5 and 1: 6), while the duration of the reaction is composed of three levels (15, 30, and 60 minutes). Parameter observations include yield, density, and viscosity of biodiesel produced. Each unit of experiment was performed using 100 ml of coconut oil and each treatment was repeated three times. The results showed that duration factor significantly influence the yield and viscosity of biodiesel, while the molar ratio factor significantly influence the viscosity of biodiesel. Interaction of these factors, however, do not affect parameters observed. The highest yield of biodiesel (75.56%) resulted within duration of 60 minutes and the lowest (60.27%) on within duration of 15 minutes. Biodiesel produced has a density of 0.86 to 0.87 g/ml (complies SNI), and a viscosity of between 3.40 to 4.55 cSt